FAKTOR-FAKTOR KESELAMATAN PENGOPERASIAN ALAT TANGKAP PURSE SEINE DI KEPULAUAN RIAU - Suci Asrina Ikhsan; Rangga Bayu Kusuma Haris; Alif Pasya Maulidanny (Universitas Teuku Umar, 2021)
Safety work on board in connection with capture fisheries specifically has the aim of preventing or reducing accidents and their consequences in the possibility of hazards and risks when carrying out activities on board. The purpose of this study was to describe the fishing operation activities using purse seine fishing gear that can pose risks and identify opportunities for failure and possible consequences that will occur when carrying out fishing activities and to determine the role of safety work on board. The research method used Hierarchical Task Analysis (HTA) to examine every activity involved in the operation of the purse seine fishing gear by dividing each activity into sub-activities carried out in the plan and descriptively utilizing problem-solving procedures investigated by describing the condition of the subject or object. The operation of purse seine fishing gear in Batam City has the potential to cause fatigue, injury, drowning, injury consequences. There are 58 activities out of 8 activity stages in the operation of the purse seine fishing gear with a Total Work Intensity (IKT) value of 557 OA (Activity Person). The value of Primary Work Intensity (IKP) at the hauling stage was the highest (0.317) with a total work intensity of 154 OA.